Effect of Support Properties on Selective Butanediols Production from Erythritol using Ir/ReOx Catalysts - Virgilio, Emanuel Martin (2021)
This study reports the selective obtaining of butanediols (BDO), widely used in the polymer and synthetic rubber industry, by C−O hydrogenolysis of erythritol. The effect of the support on catalytic activity and selectivity to BDO was exhaustively studied using Ir/ReOx catalysts supported on SiO2, Al2O3, activated carbon, CeO2, TiO2 and ZrO2. The catalysts were thoroughly characterized and it was found that the physicochemical, redox and acidic properties of the supports notably influenced the metal dispersion, reducibility of the species and particle sizes. The most active and selective catalyst was Ir/ReOx/TiO2 (maximum BDO yield of 53 %), favoring C−O hydrogenolysis and minimizing C−C scissions and dehydration reactions. This superior performance was attributed to the formation of small clusters with an intimate contact between Ir and partially oxidized Re species (mainly Re+IV) that favors the appropriate adsorption of erythritol on ReO2 and the further interaction with H2 adsorbed on Ir0 to render BDO.